Establishing company level fishing revenue and profit losses from fisheries: A bottom-up approach. - Tim Cashion; Santiago de la Puente; Dyhia Belhabib; Daniel Pauly; Dirk Zeller; U Rashid Sumaila (PLoS ONE, 2018)
A third of global fish stocks are overexploited and many are economically underperforming, resulting in potential unrealized net economic benefits of USD 51 to 83 billion annually. However, this aggregate view, while useful for global policy discussion, may obscure the view for those actors who engage at a regional level. Therefore, we develop a method to associate large companies with their fishing operations and evaluate the biological sustainability of these operations. We link current fish biomass levels and landings to the revenue streams of the companies under study to compute potentially unrealized fisheries revenues and profits at the level of individual firms. We illustrate our method using two case studies: anchoveta (Engraulis ringens; Engraulidae) in Peru and menhaden in the USA (Brevoortia patronus and B. tyrannus; Clupeidae). We demonstrate that both these fisheries could potentially increase their revenues compared to the current levels of exploitation. We estimate the net but unrealized fishery benefits for the companies under question. This information could be useful to investors and business owners who might want to be aware of the actual fisheries performance options of the companies they invest in.